Caryolene-forming carbocation rearrangements - Nguyen, Quynh Nhu N.; Tantillo, Dean J. (Beilstein Journal of Organic Chemistry, 2013)
Density functional theory calculations on mechanisms of the formation of caryolene, a putative biosynthetic precursor to caryol-1(11)-en-10-ol, reveal two mechanisms for caryolene formation: one involves a base-catalyzed deprotonation/reprotonation sequence and tertiary carbocation minimum, whereas the other (with a higher energy barrier) involves intramolecular proton transfer and the generation of a secondary carbocation minimum and a hydrogen-bridged minimum. Both mechanisms are predicted to involve concerted suprafacial/suprafacial [2 + 2] cycloadditions, whose asynchronicity allows them to avoid the constraints of orbital symmetry.
Keywords: carbocation; cycloaddition; density functional theory; mechanism; reactive intermediates; terpene